Ultrasensitive-electrochemical sensor for the detection of luteolin in Chrysanthemums and Peanut shells using an Au/Pd/reduced graphene oxide nanofilm. Issue 33 (10th August 2016) - Huang, Qitong; Lin, Xiaofeng; Lin, Changqing; Zhang, Yong; Zhang, Hanqiang; Hu, Shirong; Wei, Chan; Tong, Qing-Xiao
Abstract : In this study, a rapid and ultrasensitive luteolin sensor has been developed based on an Au/Pd/reduced graphene oxide (Au/Pd/rGO) nanofilm modified glassy carbon electrode (GCE). Abstract : In this study, a rapid and ultrasensitive luteolin sensor has been developed based on an Au/Pd/reduced graphene oxide (Au/Pd/rGO) nanofilm modified glassy carbon electrode (GCE). A green and facile method was used for the synthesis of Au/Pd/rGO, in which the groups on GO, for example, hydroxyls, epoxides and carboxyls, are used for the in situ anchoring of Au/Pd bimetallic nanocrystal precursors, which are further reduced to form an Au/Pd/rGO nanofilm. Under optimized conditions, the Au/Pd/rGO/GCE demonstrated a more excellent electrochemical response for the determination of luteolin than GCE, Au/rGO/GCE and Pd/rGO/GCE. This luteolin sensor has a linear range from 0.01 to 80.0 μM and a detection limit of 0.98 nM. In addition, the sensor was also applied to determine luteolin in Chrysanthemums and Peanut shells with satisfactory results. The proposed sensor has good stability for three months.